The why, what, who and how of scaling agricultural innovations: Key messages from the CCAFS SEA and cross-CRP Scaling Conference, Hanoi 2018 - Koerner, Jana; Woltering, Lennart; Uhlenbrock, Silke; Ohmstedt, Uwe; Zeiske, Felix; Sartas, Murat; Theissen, Arne H. (2018)
The brief discusses the key messages that transpired during the Conference on Scaling held on 29─30 November 2018 at the Melia Hotel in Hanoi, hosted by CCAFS SEA, co-hosted by ACIAR and GIZ, and funded by a CCAFS Small Grant Cross-CRP Networking. The conference main points include: scaling up agricultural innovations takes place in complex systems of agricultural transformation; and sustainable scaling should build into “sustainable change at scale”.